Hayek's social and economic philosophy - Barry, Norman P. (London : Macmillan, 1979)
Following the revival of Hayek's reputation as an economist, political philosopher and intellectual historian, this book shows why this revival has taken place, with contributions and critical assessments from internationally known scholars.
Includes index.
Includes bibliographical references: p. 220-223.
aia 09/04/2018
Loans
Keywords: Hayek, Friedrich A. von; Hayek, F. A. (Friedrich August) 1899-1992.; Social sciences $1 (BTheories of Hayek, Friedrich Augusts; Social sciences $1 (Btheories $1 (Bcritical studiess